Nutritional and metabolic derangements in Mediterranean cancer patients and survivors: the ECPC 2016 survey. Issue 3 (5th April 2019) - Muscaritoli, Maurizio; Molfino, Alessio; Scala, Ferdinando; Christoforidi, Kalliopi; Manneh‐Vangramberen, Isabelle; De Lorenzo, Francesco
Abstract: Background: The prevalence of nutritional derangements in patients with cancer is high. This survey assessed patients' awareness of cancer‐related nutritional issues and evaluated how important they perceive the impact of nutrition on cancer and treatment to be. Methods: A structured questionnaire was developed to determine: presence of feeding problems, perception of nutrition importance, and perception of physicians' approach to nutrition. The European Cancer Patient Coalition disseminated the questionnaire to its members in 10 countries. The Mediterranean cluster (Italy, Spain, and Greece) was analysed separately to further determine specific patterns in answers. Results: In total, 907 respondents completed the questionnaire (68.8% female participants; 51.7% with cancer; 48.3% cancer survivors; 59.3% diagnosed with cancer ≤3 years ago; 46.2% receiving treatment for <1 year). Feeding problems during illness/therapy were experienced by 72.5% (628/867) of all respondents (Italian: 90.0%, 117/130), although up to 53.9% (467/867) reported that physicians did not check their feeding status. Overall, 69.6% (586/842) of respondents reported weight loss after cancer diagnosis (moderate to severe: 36.7%, 309/842). For Italian respondents, the percentages of overall weight loss and moderate‐to‐severe weight loss were 85.1% (109/128) and 70.3% (90/128), respectively. Only 35.0% (295/842) of all respondents reported having their weight measured regularly during treatment; 45.7% (385/842) believed their physician considered cancer‐related weight loss unimportant. Respondents [all: 56.9% (472/830); Italian: 73.0% (92/126); Spanish: 68.9% (42/61); Greek: 79.7% (47/59)] were unaware of supplements' negative effects during therapy or the need to inform their physician about these supplements [all: 43.6% (362/830); Italian: 55.6% (70/126); Spanish: 47.5% (29/61); Greek: 49.2% (29/59)]. The term 'cachexia' was generally unknown to respondents [all: 72.9% (603/827); Italian: 64.3% (81/126); Spanish: 68.9% (42/61); Greek: 47.5% (28/59)] and most respondents [all: 92.4% (764/827); Italian: 91.3% (115/126); Spanish: 91.8% (56/61); Greek: 86.4% (51/59)] received no cachexia‐related information. Conclusions: Patients reported differences in perspective between them and physicians on cancer‐related nutritional issues and the specific nutritional approaches available for cancer treatment. Increasing physician focus on nutrition during treatment, particularly among Italian physicians, and providing information on optimizing nutrition to patients are essential factors to improving patients' quality of life.